(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
The paper presents the results of a study aimed at identifying signs corrosion damage, conditions for monitoring and diagnosing the technical condition of metal structures according to the level corrosion hazard. The paper presents the results of a study aimed at identifying signs corrosion damage, conditions for monitoring and diagnosing the technical condition of metal structures according to the level corrosion hazard. Current state of constructions supporting tower the pipe, the operation which occurs in environments of chemical production Principles process approach are used to implement the tasks of managing e service life in corrosive aggressive environments. The study identified measures to ensure durability in accordance with the level of corrosion hazard a building object, identified critical indicators secondary protection of metal structures under the conditions corrosion impacts, within the interval estimates of the values considered indicators. The determination residual resource and the adoption decisions on the further operation facility is carried out in accordance with the established patterns changing the parameters obtained by analyzing mechanisms damage development and by determining the functional quality indicators. Assigned measures of secondary corrosion protection by the criterion corrosion hazard allow us to ensure reliability requirements and compliance with the regulatory provisions of the quality of metal structures based on the solution tasks r managing technological safety for a specified period. The list of tasks to be solved includes: identifying deviations from the requirements of current regulatory documents on corrosion protection; assess the conformity of quality indicators, constructive fitness and technological rationality means methods of corrosion protection to a given level corrosion hazard; determine the requirements for the selection of materials and protective systems for metal structures according to the classification features regulatory requirements; to develop proposals for the use of tools and methods corrosion protection based on the examination of new materials and technologies for the assessment compliance with the requirements reliability and efficiency.